ATP Releasing Connexin 30 Hemichannels Mediate Flow-Induced Calcium Signaling in the Collecting Duct - Svenningsen, Per; Burford, James; Peti-Peterdi, Janos (Frontiers in Physiology, 2013)
ATP in the renal tubular fluid is an important regulator of salt and water reabsorption via purinergic calcium signaling that involves the P2Y2 receptor, ENaC and AQP2. Recently, we have shown that connexin (Cx) 30 hemichannels are localized to the non-junctional apical membrane of cells in the distal nephron-collecting duct (CD) and release ATP into the tubular fluid upon mechanical stimuli, leading to reduced salt and water reabsorption. Cx30-/- mice show salt-dependent elevations in BP and impaired pressure-natriuresis. Thus, we hypothesized that increased tubular flow rate leads to Cx30-dependent purinergic intracellular calcium ([Ca2+]i) signaling in the CD. Cortical CDs (CCDs) from wild type and Cx30-/- mice were freshly dissected and microperfused in vitro. Using confocal fluorescence imaging and the calcium-sensitive fluorophore pair Fluo-4 and Fura Red, we found that increasing tubular flow rate from 2 to 20 nl/min caused a significant 2.1-fold elevation in [Ca2+]i in wild type CCDs. This response was blunted in Cx30-/- CCDs ([Ca2+]i increased only 1.2-fold, p